1997
DOI: 10.1111/j.1751-1097.1997.tb01940.x
|View full text |Cite
|
Sign up to set email alerts
|

Phthalocyanine Photodynamic Therapy: Disparate Effects of Pharmacologic Inhibitors on Cutaneous Photosensitivity and on Tumor Regression

Abstract: The phthalocyanines are promising second-generation photosensitizers that are being evaluated for the photodynamic therapy (PDT) of malignant tumors. In vivo studies with the silicon phthalocyanine Pc 4 have shown that it is highly effective at causing regression of RIF-1 tumors in C3H/HeN mice in PDT protocols. Because cutaneous photosensitivity is the major complication of photosensitizers used for PDT, experiments were performed to evaluate the effect of inhibitors of the inflammatory response (cyproheptadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
1
2

Year Published

1998
1998
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 35 publications
0
35
1
2
Order By: Relevance
“…Accordingly, TNF-a gene transcription increased in keratinocytes sensitized with Pc 4 [258], and thioglycolateelicited murine macrophages released TNF when subjected to PDT with Photofrin II [259]. Photodynamic activation of the monocyte cell line U937 differentiated into macrophages (U937A cells) with mTHPC (FoscanR) also induced a dosedependent production of TNF-a [167].…”
Section: Anti-oxidant Enzymes and Apoptosis Regulatory Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, TNF-a gene transcription increased in keratinocytes sensitized with Pc 4 [258], and thioglycolateelicited murine macrophages released TNF when subjected to PDT with Photofrin II [259]. Photodynamic activation of the monocyte cell line U937 differentiated into macrophages (U937A cells) with mTHPC (FoscanR) also induced a dosedependent production of TNF-a [167].…”
Section: Anti-oxidant Enzymes and Apoptosis Regulatory Proteinsmentioning
confidence: 99%
“…Photodynamic activation of the monocyte cell line U937 differentiated into macrophages (U937A cells) with mTHPC (FoscanR) also induced a dosedependent production of TNF-a [167]. However, although anti-TNF-a antibodies and pentoxifylline, an inhibitor of cytokine transcription, prevented cutaneous photosensitivity in adult C3H/HeN mice injected with Pc 4, none of these agents affected Pc 4 PDT-induced tumor (RIF-1 radiationinduced fibrosarcoma) regression [258].…”
Section: Anti-oxidant Enzymes and Apoptosis Regulatory Proteinsmentioning
confidence: 99%
“…indomethacin) have been shown to reduce the cytotoxicity of PDT [30]. However, in contrast, a recent study in mice evaluating dexamethasone in conjunction with PDT reported fewer adverse effects for PDT, with unaffected cytotoxicity [31]. Further work is required to evaluate the potential of such adjuvant treatments in combination with clinical ALA PDT.…”
Section: Discussionmentioning
confidence: 99%
“…It is an important mediator of cutaneous inflammation and is produced by keratinocytes after stimulation, such as with UV light. In previous studies, TNF-α gene transcription was found to increase in the keratinocytes of mice treated with phthalocyanine and light 13 , and the expression of TNF-α protein was reported to increase up to 2.3-fold in cultured keratinocytes treated with sublethal doses of ALA and red light 5 .…”
Section: Discussionmentioning
confidence: 99%